Novel DDR2 mutation identified by whole exome sequencing in a Moroccan patient with spondylo‐meta‐epiphyseal dysplasia, short limb‐abnormal calcification type. Issue 2 (13th October 2015) - Mansouri, Maria; Kayserili, Hülya; Elalaoui, Siham Chafai; Nishimura, Gen; Iida, Aritoshi; Lyahyai, Jaber; Miyake, Noriko; Matsumoto, Naomichi; Sefiani, Abdelaziz; Ikegawa, Shiro
Abstract : Spondylo‐meta‐epiphyseal dysplasia (SMED), short limb‐abnormal calcification type (SMED, SL‐AC), is a very rare autosomal recessive disorder with various skeletal changes characterized by premature calcification leading to severe disproportionate short stature. Twenty‐two patients have been reported until now, but only five mutations (four missense and one splice‐site) in the conserved sequence encoding the tyrosine kinase domain of the DDR2 gene has been identified. We report here a novel DDR2 missense mutation, c.370C > T (p.Arg124Trp) in a Moroccan girl with SMED, SL‐AC, identified by whole exome sequencing. Our study has expanded the mutational spectrum of this rare disease and it has shown that exome sequencing is a powerful and cost‐effective tool for the diagnosis of clinically heterogeneous disorders such as SMED. © 2015 Wiley Periodicals, Inc.